2006
DOI: 10.5713/ajas.2006.1342
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fimbrial Antigen (K88 variants, K99 and 987P) of Enterotoxigenic Escherichia Coli from Neonatal and Post-weaning Piglets with Diarrhea in Central China

Abstract: Enterotoxigenic Escherichia coli is a major cause of diarrhea in neonatal and post-weaning piglets. To determine the most common fimbrial antigens of ETEC in piglets with diarrhea, two investigations were carried out on intensive pig farms in Hubei province, central China. In 2002-2003 fecal samples from neonatal and post-weaning piglets with diarrhea were tested for the presence of the fimbrial antigen K88 and K99 of ETEC by the polymerase chain reaction (PCR). Twenty-three (10.1%) of 227 fecal samples were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The prevalence of ETEC K99 was 10.36%. Similar result was reported previously by Wang et al (2006). However, higher prevalence was reported by Bendali et al (1999) and Achá et al (2004) who reported a prevalence rate of 20.3% and 16%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of ETEC K99 was 10.36%. Similar result was reported previously by Wang et al (2006). However, higher prevalence was reported by Bendali et al (1999) and Achá et al (2004) who reported a prevalence rate of 20.3% and 16%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas the two variants F18ab and F18ac recognize the same receptor (Rippinger et al 1995), the three variants of F4 vary in their receptor specificities (Bijlsma et al 1982). However, F4ac is by far the most prevalent variant all over the world with the exception of central China, where F4ad is reported to be predominant (Wang et al 2006). Fortunately, the causative mutation for E. coli F18 susceptibility is known (Meijerink et al 1997(Meijerink et al , 2000 and elimination of the E. coli F18 susceptibility allele from the porcine population is currently done in Switzerland and other countries to increase the number of resistant piglets in commercial populations (Luther et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The 987P-positive bacterium is one of the enterotoxigenic Escherichia coli (ETEC) strains that cause diarrhoea in neonatal piglets (Deannystrom and Samuel, 1994;Wang et al, 2006). It was reported to cause diarrhoea through direct delivery of toxins to host enterocytes after binding to brush borders by means of adhesive proteins in fimbriae (Nataro and Kaper, 1998).…”
Section: Introductionmentioning
confidence: 98%